The neurologist’s hammer - Nogueira, Eduardo (2019)
From the obscurity of 18th century wineries to the hands of the greatest neurologists in history, the percussion hammer has a fascinating history. The first famous percussion hammer was created in 1841 by the German physician Max Wintrich and was initially used for thoracic percussion. In 1875, Erb and Westphal both published simultaneous articles with the results from research that they had conducted separately, from which they confirmed that percussive objects were useful for stimulating deep tendon reflexes, especially patellar reflexes. The percussion hammer, however, was not yet ideal. It was designed to strike the thorax rather than the tendons, so it did not have the right weight or ideal length, and even its shape was not practical. New modified versions of the instrument subsequently emerged, and the hammer became the characteristic symbol of the neurologist.